ASSOCIATION BETWEEN KNOWLEDGE AND BEHAVIOR IN MAINTAINING ORAL HYGIENE WITH DENTAL CARIES AMONG CHILDREN IN GIANYAR - Winarno, Heidar Rauf; Nasution, Vivien Aulia Hadi; Chandra, Rizky Mega; Adiningsih, Ni Ketut Sri; Anggaraeni, Ni Made Yuliana; Handoko, Steffano Aditya; Putri, Wayan Citra Wulan Sucipta (Essential: Essence of Scientific Medical Journal, 2018)
Background: The prevalence of dental caries among children in South East Asia, Indonesia, and Bali was 95%, 72%, and 22.5%, respectively. Dental caries in children can lead to another serious comorbidity of systemic problem such as diabetes and cardiovascular disease. The development of dental caries among children is influenced by their knowledge and behavior in maintaining oral hygiene. Purpose: The purpose of this study was to determine the association of knowledge and behavior in maintaining oral hygiene with dental caries status among children in Gianyar, Bali. Method: A Cross-sectional analytic study design was used to determine the association between the variables. The sample size of this study was 70 and consist of 7-8 years old state elementary school children. Bivariate and multivariate statistical analysis was performed in this study. Results: This study showed that 94.3% of the participant had dental caries. There is no significant association between knowledge in maintaining oral hygiene and dental caries (P=0.743). However, there is a significant association between behavior in maintaining oral hygiene and dental caries (P=0.011). Conclusion: Poor behavior and knowledge in maintaining oral hygiene among children are not associated with the presence of dental caries. However, education and practice lesson in maintaining oral hygiene should be directed to the lower categories of each group.